Welding of High Entropy Alloys - Shen, Jiajia (2022)
High entropy alloys are novel engineering materials which possess extraordinary properties. Current weldability studies regarding this novel class of materials are scarce. Hence, the present work addresses this shortcoming by focusing on the use of arc-based welding processes for joining of single phase equiatomic CoCrFeMnNi (Co-Cr-Fe-Mn-Ni system), a dual phase non-equiatomic eutectic AlCoCrFeNi2.1 (Al-Co-Cr-Fe-Ni system) and a metastable Fe42Mn28Co10Cr15Si5 (Fe-Mn-Co-Cr-Si system) high entropy alloys. For the single phase CoCrFeMnNi, gas metal arc welding using 308 and 410 stainless steel fillers are used. Multiscale correlative microstructure characterization encompassing electron microscopy coupled with mechanical property analysis, alongside thermodynamic calculations, is used to address the effect of the weld thermal cycle across the joint. Overall, this material possesses excellent weldability, with the joints possessing good mechanical behavior. The first successful welding of a non-equiatomic eutectic AlCoCrFeNi2.1 is obtained using gas tungsten arc welding. Again, multiscale characterization enabled to determine the role of the weld thermal cycle across the welded joint. The volume fraction of the dual-phase structure, as well as those of the strengthening nanoscale precipitates was seen to be correlated to the distance to the heat source. The as-welded material possessed a combination of good strength and ductility, showcasing the good weldability of this material. Finally, gas tungsten arc welding of a metastable Fe42Mn28Co10Cr15Si5 was also successfully performed. Electron microscopy, aided by high energy synchrotron X-ray diffraction, were combined with thermodynamic calculation to understand how the existing phases varied across the welded joint. Similarly, to the other welded joints, the metastable alloy was also seen to present good weldability, with the observed mechanical behavior of the joints enabling its use for structural applications in different industries. The results obtained in this work show that arc-based welding processes are viable for welding of these novel materials and the resulting properties enable to consider the obtained joints for structural-oriented applications.